1991
DOI: 10.1002/1097-0142(19910415)67:8<2200::aid-cncr2820670833>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal prostate-specific antigen in untreated prostate cancer. Relationship to clinical stage and grade

Abstract: The authors evaluated 440 men with clinically staged and untreated prostate cancer with a monoclonal prostate-specific antigen (PSA) assay. The serum PSA value correlated significantly with both the stage and grade of disease (P < 0.00005). The relationships between PSA and consecutive Stages A, B, C, and D, (a = 0.15) and between progressive Gleason's scores 2 to 4, 5 to 7, and 8 to 10 (a = 0.15) were statistically significant. Also statistically significant was the correlation between serum PSA level and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…2 only 7% of the patients had cancer. Babaian and Camps [6] reported similar results, finding a 23.1 % and 19.6% cancer incidence in men with an abnormal DRE (regardless of TRUS) and an abnormal TRUS (regardless of DRE), respectively, if the PSA was 9 4 compared to 77.8% and 71.2%, respectively, if the PSA was >4.…”
Section: Discussionmentioning
confidence: 94%
“…2 only 7% of the patients had cancer. Babaian and Camps [6] reported similar results, finding a 23.1 % and 19.6% cancer incidence in men with an abnormal DRE (regardless of TRUS) and an abnormal TRUS (regardless of DRE), respectively, if the PSA was 9 4 compared to 77.8% and 71.2%, respectively, if the PSA was >4.…”
Section: Discussionmentioning
confidence: 94%
“…This may be especially true for older men who have coexistent benign prostatic hyperplasia (BPH), which may elevate the PSA level even though prostate cancer may not be present. Even though older men have a higher incidence of prostate cancer, previous studies have reported that BPH is accompanied by PSA levels >4 ng/ ml in 25-53% of cases [11,12]. Thus, using a 4.0-ng/ml cutoff PSA value would give a higher false-positive rate and a lower PPV.…”
Section: Discussionmentioning
confidence: 98%
“…These investigators noted that both the presence and intensity of PSA staining inversely correlated with the Gleason grade of the tumour [9]. Other studies have shown a similar correlation of PSA level with grade [28], and have noted poor expression of PSA in high‐grade cancers [7,10,29], although smaller, or exclusively serum‐based, studies have found no consistent correlation of PSA expression with grade [30].…”
Section: Discussionmentioning
confidence: 99%